Polygenetic errors in the Ethiopic Witnesses of the Epistle to the Galatians and Three Groups of Ethiopic Manuscripts in the Light of Galatians 6:14 - Kebede, Fikremariam Bazezew (e-Journal of Linguistics; Vol 18 No 2 (2024): ejl-JulyDO - 10.24843/e-jl.2024.v18.i02.p01, 2024)
As part of the preparation of a critical edition of the Epistle to the Galatians in its Ge’ez version one needs to examine various manuscripts. Exploring 16 Ge’ez manuscripts the author has collated all types of variants and come up with the hypothesis of three different groups of Ethiopian manuscripts as far as the Epistle to the Galatians is concerned. Just as some variants like Galatians 6:14 help to identify groups of manuscripts, the majority of variants are not caused by scribal dependence on earlier manuscripts. In other words, the innovations and errors are polygenetic, namely the fruit of independent scribal activities. This article presents such variants, classified according to transposition, banalization, incongruity of grammatical number, omission of letters, polar errors, and metathesis.